بناء برنامج لتدريب معلمات القرآن الكريم في أثناء الخدمة بالمرحلة الابتدائية بالمملكة العربية السعودية: تصور مقترح - الطويرقي، حنان محمد عبدالله (جامعة عين شمس - كلية التربية - الجمعية المصرية للمناهج وطرق التدريس, 2011)
هدفت هذه الدراسة إلى وضع تصور مقترح لبرنامج تدريب المعلمات اللاتي يدرسنا القرآن الكريم في المرحلة الابتدائية وفق الاحتياجات التدريبية والتي كشفت عنها الدراسات السابقة ولتحقيق أهداف الدراسة قامت الباحثة باستخدام المنهج الوصفي للتعرف على طبيعة القرآن الكريم وأهمية تدريسه وطبيعة المرحلة الابتدائية، ثم الوقوف على معنى التدريب وأهدافه وأنواعه وأساليبه وأهم الاتجاهات المعاصر في تدريب المعلمات أثناء الخدمة وتحديد الاحتياجات التدريبية لمعلمات القرآن الكريم من خلال الدراسات السابقة، ثم وضع التصور المقترح للبرنامج التدريبي وفق الأسس العلمية لبناء البرنامج وفي ضوء الاحتياجات التدريبية لمعلمات القرآن الكريم والتي كشفت عنها الدراسات السابقة وأسفرت نتائج الدراسة عن الآتي: \ \ ضرورة بناء برامج تدريبية لمعلمات القرآن الكريم بمختلف أنواعها للرفع من كفايتهن التربوية والتخصصية مبنية على أسس علمية مدروسة تهتم بالجوانب العملية والتطبيقية بالإضافة للجوانب المعرفية والنظريات العلمية مع الاهتمام باستخدام التقنيات التعليمية الحديثة. \ \ وكان من أبرز توصيات ومقترحات الدراسة ما يلي: \ 1)\ صياغة برامج التدريب لمعلمات القرآن الكريم بالمرحلة الابتدائية في المملكة العربية السعودية بمختلف أنواعها للرفع من كفاءتهن وتمكينهن من القيام بمسؤولياتهن المتوقعة منهن. \ 2)\ عقد برامج التدريب لهن بصورة منتظمة ومستمرة لتحقيق مفهوم التربية المستمرة وربطهن بما يستجد في العلوم التربوية. \ 3)\ إنشاء مراكز للتدريب مجهز بكافة المواد والوسائل والأجهزة وتدعيمها بالكوادر المتخصصة والمؤهلة في مجال التدريب. \ 4)\ دراسة تتعلق بالجوانب التنظيمية للبرنامج المقترح مما لم تشمله هذه الدراسة كتحديد وقته ومكانة وطريقة تمويله. The Topic of the Study: To build a program for training The Holy Qur'an teachers while working in the primary stage in the Kingdom of Saudi Arabia. The researcher clarified the problem of the study in one question which is: "How can a program for Holy Qur'an teachers in the primary stage be build according to their needs in training which is clarified from previous studies. To reach this goal, researcher used the descriptive approach to identify the nature of the Holy Qur'an, the importance of teaching it and the nature of the primary stage. Then to stand on the meaning of training, its aim, its way and kinds. And The most important contemporary trends in training teachers while working and pointing out their needs in training for Holy Qur'an teachers from previous studies. Then , develop the concept of the proposal for a training program according to scientific basics for building a program in the behalf of the training needs for Holy Qur'an teachers that previous studies clarified. \ Results of the study were as follow The importance for building a training program for the Holy Qur'an chers in different kinds to raise their educational and specialized efficiency based on scientific thoughts which takes care of scientific and applied aspects, knowledge and theory sides with taking care of the use of modem technology. The highlights of the recommendations and proposals was the following \ •\ Drafting a program for training the Holy Qur'an teachers in the primary stage in The Kingdom of Saudi Arabia in different aspects to raise their capabilities and enable them to do their expected responsibilities. \ •\ Making training programs in a regular and continuous way to achieve the aim of continuing education and linking them with the development of educational science. \ •\ Establishing training centers equipped with all the materials, methods, specialized devices and qualified people in the field of training. \ •\ Make a study in the organization aspects of the proposed program which this study didn't mention like pointing a specific time, place and way of financing the program.
608063
Keywords: السعودية -- البرامج التدريبية -- اعداد المعلمين -- القرآن الكريم -- التعليم الأساسي -- تحفيظ القرآن الكريم -- التقويم التربوي -- التخطيط التربوي -- تدريب المعلمين اثناء الخدمة -- تنمية المهارات -- تدريب المعلمات -- الاحتياجات التدريبية -- الوسائل التعليمية